2007
DOI: 10.1002/esp.1582
|View full text |Cite
|
Sign up to set email alerts
|

Aeolian fetch distance and secondary airflow effects: the influence of micro‐scale variables on meso‐scale foredune development

Abstract: Unsuccessful attempts to use process-scale models to predict long-term aeolian sediment transport patterns have long been a feature of aeolian research. It has been proposed that one approach to overcome these problems is to identify micro-scale variables that are important at longer timescales. This paper assesses the contribution of two system variables (secondary airflow patterns and fetch distance) to medium-term (months to years) dune development. The micro-scale importance of these variables had been est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 47 publications
6
41
0
1
Order By: Relevance
“…The net movement, however, was seen to be onshore with ripple crest orientation and dune foot trap data presented as evidence. Further to this work, Lynch et al (2008) have reported on post-storm recovery at this site over a 2-year period -under characteristically dominant offshore winds.…”
Section: Wind Approach Angle Thresholds For Airfl Ow Separationmentioning
confidence: 91%
“…The net movement, however, was seen to be onshore with ripple crest orientation and dune foot trap data presented as evidence. Further to this work, Lynch et al (2008) have reported on post-storm recovery at this site over a 2-year period -under characteristically dominant offshore winds.…”
Section: Wind Approach Angle Thresholds For Airfl Ow Separationmentioning
confidence: 91%
“…In particular, these field experiments demonstrated that offshore flow can be substantially modified in the lee of a large coastal foredune, to the extent that shore-parallel steering and eddy recirculation occurs on the beach (Lynch et al, 2008;Bauer et al, 2012) as recognized by Hesp (2005).…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…This approach is still being developed in the literature and remains the only way to improve knowledge of the coastal processes and interactions (Stive et al, 2002). Even if these theoretical links are difficult to substantiate (Sherman, 1995;Lynch et al, 2008), they should be an important focus of future research by coastal geomorphologists.…”
Section: Discussionmentioning
confidence: 99%
“…K.F. Nordstrom et al, (1996) indicate an abscence of sand transport around the dune toe while K. Lynch et al (2008) highlight a change in flow direction and a possible reverseal. Nevertheless, both cases investigated involved high dunes (>10 m) which are not directly comparable with the low dune systems of the erosional shores of Camargue.…”
Section: The Southern North Sea Coast: Beach/dune/shoreface Articulatmentioning
confidence: 99%